OLD HABITS VS. NEW DEMANDS: CHALLENGES IN REFORMING TOP MANAGERS IN THE MACEDONIAN PUBLIC ADMINISTRATION - Pavlovska Daneva, Ana; Bitrakov, Konstantin (Iustinianus Primus Faculty of Law, 2025)
significant factor in determining whether a country will thrive is the quality of its public administration. Citizens are far more likely to enjoy a higher quality of life if their country’s public administration has the capacity to fulfill its duties effectively and perform optimally. The business sector is more likely to develop when the public administration operates smoothly and provides stability, as well as quick and accessible services. The civil sector, likewise, can rely on a capable and responsive partner if the public administration functions transparently and efficiently. In other words, the institutions falling under the umbrella term “public administration” are responsible for enforcing the law (while considering both individual rights and the public interest), implementing policies, supervising compliance with regulations by citizens and legal entities, delivering public services, and more. For that reason, they play a vital role in ensuring citizens’ well-being, fostering a business-friendly environment, and contributing to the development and success of the civil sector. Given this, it is essential that these institutions are properly managed. This requires top public managers who are competent, informed, well-equipped, responsible, and sufficiently independent. In this context, the paper at hand examines top public managers in the Republic of North Macedonia. It explores not only the legal framework governing managers in the public administration (also referred to as top public managers, office holders, elected and appointed persons, or functionaries), but also the actual practices concerning their recruitment, performance evaluation, accountability, and dismissal. The suggestions the authors provide throughout the paper are envisaged as a remedy against the systemic weaknesses that have been identified and that are elaborated upon herein.